Józef Szujski ( 1835-1883) o badaniach nad pierwostanem człowieka - Abramowicz, Andrzej (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
Since 1863 information about the discoveries made by Jacques Boucher de Perthes and other scholars and proving the great antiquity of man and his culture began to reach Poland, at that time still occupied by Russia, Austria and Prussia as a result of partitions that took place in the previous century. The extention of the history of man and the evidence of the gradual development of human culture could not leave Polish historians indifferent. In 1867 opinion on this subject was given by Józef Szujski, one of the founders of the Cracow school of history, later professor in the Department of the History of Poland, founded in 1869 at the Jagiellonian University of Cracow, the secretary of the Academy of Learning, writer and conservative politician. His article: Badania nad pierwostanem człowieka (Study of the primeval state of man) was published in the conservative periodical „Przegląd Polski". In this paper Szujski emphatically opposed the use of Darvinian evolutionism in the study of the earliest history of man and his culture. Though he recognized the fact that man had encountered some species of animals now extinct and that in Western Europe the bones of these animals were occasionally accompanied by primitive artifacts, he tended to think that it was a trace of degenerated human groups cut off from the great stock of humankind „growing on the upland of Iran or on the Mesopotamian plain". Szujski advocated the possibly shortest chronology and thought following Rheinhold Pallmann - that the youngest Swiss pile dwellings contained Roman relics. Son of the Catholic Church, he presents the origin of man and his culture according to the spirit of the Church’s teaching of those days.